Uncontrolled logic: intuitive sensitivity to logical structure in random responding. (27th January 2022) - Howarth, Stephanie; Handley, Simon; Polito, Vince
Abstract: It is well established that beliefs provide powerful cues that influence reasoning. Over the last decade research has revealed that judgments based upon logical structure may also pre-empt deliberative reasoning. Evidence for 'intuitive logic' has been claimed using a range of measures (i.e. confidence ratings or latency of response on conflict problems). However, it is unclear how well such measures genuinely reflect logical intuition. In this paper we introduce a new method designed to test for evidence of intuitive logic. In two experiments participants were asked to make random judgments about the logical validity of a series of simple and complex syllogistic arguments. For simple arguments there was an effect of logical validity on random responding, which was absent for complex arguments. These findings provide a novel demonstration that people are intuitively sensitive to logical structure.